2018
DOI: 10.1002/jgm.3043
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β4 suppresses CCl4‐induced murine hepatic fibrosis by down‐regulating transforming growth factor β receptor‐II

Abstract: Tβ4 possesses anti-fibrotic activity in the liver, which is attributable, at least partly, to down-regulating TGF-βRII and thereby blunting TGF-β1-mediated fibrogenetic signaling in both HSCs and hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(97 reference statements)
1
9
0
Order By: Relevance
“…It protects against cardiac, kidney and corneal injury [53] . Herein, in agreement with the previous studies in which systemic T β 4 administration decreased the TNF-α level in mice with sepsis and with experimental colitis as well [54,55] , the present study demonstrated that T β 4 significantly reduced the elevated tissue TNF-α and IL-6 levels in the intestinal I/R injury group suggesting restoration of the balance of proinflammatory cytokines confirming the potential anti-inflammatory effect of Tβ4 in attenuating the intestinal I/R injury.…”
Section: Discussionsupporting
confidence: 92%
“…It protects against cardiac, kidney and corneal injury [53] . Herein, in agreement with the previous studies in which systemic T β 4 administration decreased the TNF-α level in mice with sepsis and with experimental colitis as well [54,55] , the present study demonstrated that T β 4 significantly reduced the elevated tissue TNF-α and IL-6 levels in the intestinal I/R injury group suggesting restoration of the balance of proinflammatory cytokines confirming the potential anti-inflammatory effect of Tβ4 in attenuating the intestinal I/R injury.…”
Section: Discussionsupporting
confidence: 92%
“…To localize TMSB4X in the E15 chick utricle, we used an antibody that has been validated previously with knock-down experiments against mouse TMSB4X (Zhou et al, 2013; Li et al, 2018); chicken TMSB4X differs from mouse and human TMSB4X by only two serine-to-threonine substitutions out of 44 total amino acids. TMSB4X immunoreactivity was cytoplasmic and strong in supporting cells and substantially reduced in hair cells (Figure 3G–I and Figure 3—figure supplement 3), which was consistent with the mass-spectrometry results.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β is a central mediator of the liver brosis process, activating transdi erentiation from HSCs to myo broblasts and producing ECM. Previous animal studies demonstrated that hepatic TGF-β overexpression increased brosis, whereas TGF-β neutralization abolished this process [34][35][36]. erefore, anti-TGF-β strategies have been developed to treat chronic liver diseases [37].…”
Section: Discussionmentioning
confidence: 99%